Factor analysis of body measurements of local cows of Manipur, India - Tolenkhomba, T C; Konsam, D S; Singh, N Shyamsana; M, Prava; Singh, Y Damodor; Ali, M Ayub; Motina, E (International Multidisciplinary Research Journal, 2012)
Eighteen different biometric traits in 250 local cows of Manipur from their breeding zone, i.e. Imphal valley of Manipur, India, were recorded and analyzed by principal component analysis to explain body conformation. The averages of height at withers (HW), body length, heart girth, paunch girth, forehead width, ear length, tail length, switch length, neck circumference, neck length, arm length, elbow length, fore-shank length, thigh length, hind-shank length, pes length, head length and eye to eye space were 103.92±0.33, 111.34±0.92, 135.34±0.47, 140.31±0.53, 14.90±0.15, 15.24±0.13, 75.50±0.55, 31.04±0.24, 58.61±0.53, 29.95±0.21, 29.34±0.19, 29.88±0.17, 29.59±0.20, 30.32±0.20, 29.88±0.13, 31.65±0.25, 37.30±0.25 and 26.47±0.20 cm, respectively. The correlation coefficients ranged from -0.20 (hind shank length and eye to eye width) to 0.74 (heart girth and paunch girth). Factor analysis with promax rotation revealed seven factors which explained about 64.31% of the total variation. Factor 1 described the general body conformation and explained 17.74% of total variation. It was represented by significant positive high loading of height at wither, heart girth, paunch girth and ear length. The remaining factors described 11.71%, 8.88%, 7.47%, 6.60%, 6.04% and 5.86% of total variability. It was necessary to include some more variables for a reliable analysis of factors as there were less than three variables except the first factor in the present study. The communality ranged from 0.493 (elbow length) to 0.782 (neck circumference) and unique factors ranged from 0.507 to 0.218 for all these 18 different biometric traits. The lower communalities for some of the traits like ear length, tail length, arm length, elbow length and thigh length might indicate that these traits were less effective to account for total variation of body conformation as compared to the other traits in local cows of Manipur. The result suggests that principal component analysis (PCA) could be used in breeding programs with a drastic reduction in the number of biometric traits to be recorded to explain body conformation.